Investigating the antidepressant effect of Ziyan green tea on chronic unpredictable mild stress mice through fecal metabolomics - Jia, Wenbao; Tang, Qian; Zou, Yao; Yang, Yang; Wu, Wenliang; Xu, Wei (Frontiers in Microbiology, 2023)
Some studies have shown the effectiveness of tea in reducing depression. Gut flora dysfunction is strongly associated with depression. The mechanism by which Ziyan green tea ameliorates depression is not clear. In this study, we examined the impact of Ziyan green tea on mice exhibiting symptoms similar to depression. We specifically focused on the role of intestinal flora and its metabolites. We first established a chronic unpredictable mild stress (CUMS) mouse model to induce depressive symptoms and conducted behavioural tests, biochemical tests, and pathological tissue analysis. We also investigated gut microbiota changes by 16S rRNA sequencing and measured faecal metabolites in mice using UHPLC-MS/MS.The results showed that Ziyan green tea intervention improved depression-like behaviour, neurobiochemical factors, and reduced levels of pro-inflammatory factors in CUMS mice. Spearman's correlation analysis showed that different microbial communities (Corynebacterium, Faecalibaculum, Enterorhabdus, Desulfovibrio) correlation with differential metabolites (Cholic acid, Deoxycholic acid, etc.) and depression-related biochemical indicators (5-HT, DA, BDNF, IL-6, and TNF-α). The results showed that Ziyan green tea could alleviate depression in mice by gut-microbiota-brain Axis.